Projection TV with improved micromirror array - HUIBERS ANDREW G (2006)
In order to minimize light diffraction along the direction of switching and more particularly light diffraction into the acceptance cone of the collection optics, in the present invention, micromirrors are provided which are not rectangular. Also, in order to minimize the cost of the illumination optics and the size of the display unit of the present invention, the light source is placed orthogonal to the rows (or columns) of the array, and/or the light source is placed orthogonal to a side of the frame defining the active area of the array. The incident light beam, though orthogonal to the sides of the active area, is not however, orthogonal to any substantial portion of sides of the individual micromirrors in the array. Orthogonal sides cause incident light to diffract along the direction of micromirror switching, and result in light 'leakage' into the 'on' state even if the micromirror is in the 'off' state. This light diffraction decreases the contrast ratio of the micromirror. The micromirrors of the present invention result in an improved contrast ratio, and the arrangement of the light source to micromirror array in the present invention results in a more compact system. Another feature of the invention is the ability of the micromirrors to pivot in opposite direction to on and off positions (the on position directing light to collection optics)-, where the movement to the on position is greater than movement to the off position. A further feature of the invention is a package for the micromirror array, the package having a window that is not parallel to the substrate upon which the micromirrors are formed. One example of the invention includes all the above features.